Transcriptome and 16S rRNA Analyses Reveal That Hypoxic Stress Affects the Antioxidant Capacity of Largemouth Bass (Micropterus salmoides), Resulting in Intestinal Tissue Damage and Structural Changes in Microflora - Zhuo Song; Wei Ye; Yifan Tao; Tao Zheng; Jun Qiang; Yan Li; Wenting Liu; Pao Xu (MDPI AG, 2022)
Dissolved oxygen (DO) is a key factor affecting the health of aquatic organisms in an intensive aquaculture environment. In this study, largemouth bass (Micropterus salmoides) were subjected to acute hypoxic stress for 96 h (DO: 1.00 mg/L) followed by recovery under sufficient DO conditions (DO: 7.50 mg/L) for 96 h. Serum biochemical indices, intestinal histomorphology, the transcriptome, and intestinal microbiota were compared between hypoxia-treated fish and those in a control group. The results showed that hypoxia caused oxidative stress, exfoliation of the intestinal villus epithelium and villus rupture, and increased cell apoptosis. Transcriptome analyses revealed that antioxidant-, inflammation-, and apoptosis-related pathways were activated, and that the MAPK signaling pathway played an important role under hypoxic stress. In addition, 16S rRNA sequencing analyses revealed that hypoxic stress significantly decreased bacterial richness and identified the dominant phyla (Proteobacteria, Firmicutes) and genera (Mycoplasma, unclassified Enterobacterales, Cetobacterium) involved in the intestinal inflammatory response of largemouth bass. Pearson's correlation analyses showed that differentially expressed genes in the MAPK signaling pathway were significantly correlated with some microflora. The results of this study will help to develop strategies to reduce damage caused by hypoxic stress in aquacultured fish.